2006
DOI: 10.1038/msb4100059
|View full text |Cite
|
Sign up to set email alerts
|

Core transcriptional regulatory circuitry in human hepatocytes

Abstract: We mapped the transcriptional regulatory circuitry for six master regulators in human hepatocytes using chromatin immunoprecipitation and high-resolution promoter microarrays. The results show that these regulators form a highly interconnected core circuitry, and reveal the local regulatory network motifs created by regulator-gene interactions. Autoregulation was a prominent theme among these regulators. We found that hepatocyte master regulators tend to bind promoter regions combinatorially and that the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
230
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(241 citation statements)
references
References 38 publications
(55 reference statements)
9
230
2
Order By: Relevance
“…SNPs rs2021722, rs2763979 and rs2075799 had )log 10 (p-value)>5. SNP rs2021722 is located within TRIM26, which has been found to directly interact with hepatocyte nuclear factor 4-a, whose misregulation contributes to type 2 diabetes [32]. SNP rs2763979 is located within HSPA1B, which also has susceptibility implications in type 2 diabetes [33] and is prevalent in southern Asians [34].…”
Section: Resultsmentioning
confidence: 99%
“…SNPs rs2021722, rs2763979 and rs2075799 had )log 10 (p-value)>5. SNP rs2021722 is located within TRIM26, which has been found to directly interact with hepatocyte nuclear factor 4-a, whose misregulation contributes to type 2 diabetes [32]. SNP rs2763979 is located within HSPA1B, which also has susceptibility implications in type 2 diabetes [33] and is prevalent in southern Asians [34].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, combining genome-wide location and microarray analysis has also helped to reveal the targets of C/EBP beta (CCAAT enhancer-binding protein beta), a basicleucine zipper transcription factor; these targets are critical to the regulation of numerous biological processes, including liver development [18]. These and other findings have demonstrated that a genomic approach is one of the key ways of screening for important candidates that are likely to control hepatocyte differentiation and liver development [19,20].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the adult ␤-cell, the expression of HNF-4␣ is regulated by the pancreatic transcription factor network (21)(22)(23), positively by a number of proteins including the HNF1A, PDX1, and HNF1B gene products (22,24,25) and negatively by itself (21). The key regulatory relationship appears to be that with HNF-1␣ (26).…”
mentioning
confidence: 99%